PENYELESAIAN WANPRESTASI DALAM PERJANJIAN PEMBORONGAN PEKERJAAN KONSTRUKSI (STUDI KASUS PEKERJAAN KONSTRUKSI REHABILITASI BANGUNAN GEDUNG KANTOR PENGADILAN TINGGI AGAMA YOGYAKARTA) - WIBOWO, ARI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Research on Miss-Achievement Settlement In The Contract Agreement Of Construction Work (Case Study Construction Work for Rehabilitation in High Relegion Court Of Yogyakarta Office Building) aims to determine the form of Miss- Achievement Settlement execution and completion of the construction work chartering agreement. This research is an deskriptif eksplanatif by relying on secondary data as the primary data source through official documents which related with the research. Field research is still being done in supporting the research literature. The data obtained from the study were analyzed qualitatively and presented descriptively. As the results showed that the form of Miss-Achievement that occurred in the execution of contract agreement between the PPK (Committing Officer) of Religious High Court of Yogyakarta with CV Tri Jaya as the provider held what in agreement but is doesn’t accordance with what was agreed. Completion of Miss-Achievement Settlement made by the issuance of a Miss-Achievement statement from the CO to the CV Tri Jaya which has an effect in the termination of the agreement between the parties and then the retention will be cashed to use as office improvements. In addition, CV Tri Jaya proposed to LKPP by CO to put in the blacklist.